Urotensin-II Receptor: A Double Identity Receptor Involved in Vasoconstriction and in the Development of Digestive Tract Cancers and other Tumors - Federico, Alessandro; Zappavigna, Silvia; Dallio, Marcello; Misso, Gabriella; Merlino, Francesco; Loguercio, Carmela; Novellino, Ettore; Grieco, Paolo; Caraglia, Michele (Current Cancer Drug Targets, 2017)
Urotensin II and Urotensin-II receptors are important molecular factors that regulate vasoconstriction and all the diseases that are linked to abnormalities in blood pressure regulation (i.e.: hypertension, kidney diseases, cirrhosis etc.). Recently, Urotensin II and its receptor have also been involved in metabolic syndrome, diabetes and schizophrenia. Recent strong findings suggest that Urotensin II and its receptor are involved in the onset and development of different epithelial cancers. Indeed, it was reported that cell growth, motility and invasion in human breast, bladder, prostate, colorectal and glioblastoma cancer cells were regulated by Urotensin II and Urotensin-II receptor axis. This axis also regulated focal adhesion kinase and small Guanosine-5'-triphosphate binding proteins that likely had a role in motility and invasion mediated by Urotensin-II receptor. Additionally, its expression on tumour tissues is variably associated to the prediction of the clinical outcome of the patients and it can be considered an alternative molecular marker to be used as prognostic factor in human cancers. In conclusion, a new weapon in the treatment of human cancers is highlighting a new scenario for the future.
Keywords: Urotensin-II receptors